CLIMATE CHANGE AND ITS IMPACT ON AGRICULTURAL PRODUCTION – A CASE STUDY IN THE TOLON DISTRICT OF GHANA - Shu-aib Jakpa, S.; Owusu, F.; Gandaa, B. Z. (UDS International Journal of Development, 2019)
This study was done in Sabegu in the Tolon District of the Northern Region of Ghana to determine the extent to which two key climatic factors, temperature and rainfall, have changed and their impact on agriculture. Temperature and rainfall data in the District over a period of twenty-one years (1995 – 2015) were gathered and analyzed. In addition, data on pepper production for three consecutive years (2013-2015) were gathered from forty-one pepper farmers using a simple random sampling method. Statistical Package for Social Sciences (SPSS) was utlized to analyze the gathered data and the results were interpreted and presented in simple descriptive statistics format. Results of the research, based on yield data provided by the farmers, indicate that with an increase in average annual temperature from 27.1oC to 27.9oC and a decrease in annual rainfall from 1000 mm to 900 mm there was a yield reduction of the crop by about 24% between 2013 and 2015. Keywords: Climate change, Temperature, Rainfall, Impact, Pepper production